Optical properties of dye DN-F05 as a good sensitizer - Diani Galih Saputri; Agus Supriyanto; Mohd Khairul Ahmad; Nadiyah El-Haq Diyanahesa; Febrina Ramadhani (Universitas Sebelas Maret, 2019)
This research studied the effect of adding synthetic dye DN-F05 (red dye) to electrical and optical properties. Dye-Sensitized Solar Cell (DSSC) sandwich components are consist of FTO/TiO2-Dye-elektrolit-Platina/FTO. In this study, the working electrodes were made by Titanium dioxide (TiO2) which was deposited on FTO glass and then annealed at 450oC for 30 minutes. The dye concentration DN-F05 was made with a mass of 0.001 gr, then will be stirred for 2 hours into 5 ml of ethanol at a temperature of 40oC. In this study the spin coating method is used with a rotational speed of 1000 rpm for 20 seconds. Characterization of optical properties was carried out using a UV-VIS spectrophotometer to determine the absorbance curve of dye and to get Gap energy. The peak absorbance value was obtained at wavelengths between 400-700 nm. This proved that the addition of DN-F05 dye concentration has a major influence on the optical properties.